Peran Pemasaran Digital dalam Memperluas Jangkauan Pasar UMKM Lesehan Angel di Era Society 5.0 - Santi Rimadias; Bani Saad; Bintang Amanda; Liviana Putri Widianto; Gabriella Septalia Konda; Muhammad Iqbal Jehansyah; Muhammad Bagas Ardhianto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The fluctuating shifts in consumer behavior in the Society 5.0 era are forcing the Micro, Small, and Medium Enterprises (MSMEs) sector to adopt digital tools. Based on this situation, the STIE Indonesia Banking School's community service program team implemented digital marketing tactics. This community service program aimed to expand the market share of the